(untitled) (Research, Society and Development, 2023)
This study aimed to describe the nutritional interventions performed by the nutritionist in the care of the sarcopenic elerly. This is a field study,observational in nature, cross-descriptive, with a quantitative approach. The survey was carried out during the months of December 2021 to February 2022, with nutritionists who work or who have worked in clinics and hospitals, through an online questionnaire in Google Forms, containing 17 objective questions. This was released by email, WhatsApp Messenger and Instagram. In the data analysis, the objective questions were exposed through graphs, in which the collected data were placed in Microsoft Excel 2013 tables, providing their comparison. The work was submitted to Plataforma Brasil and after being approved by the Ethics Committee, the research began. From the results, the sample consisted mostly of females, aged between 31 and 50 years. Nutritionists demonstrated knowledge about sarcopenia and nutritional interventions most used by them were through a hypercaloric, hyperproteic, normoglicidic and normolipidic diet, with greater emphasis on protein, calcium, vitamin D and omega 3 supplementation. However, it is important to point out that the subject is still scarce, therefore, further studies in this area are extremely relevant.